Perfil hemodinâmico materno-fetal de gestantes tabagistas crônicas: estudo doppler - Machado, Ana Paula Lino Jorge (2015)
The objective of this study was to evaluate the influence of chronic smoking on maternal-fetal hemodynamics through Doppler study of maternal uterine (UtA), fetal umbilical (UmA) and fetal middle cerebral (MCA) arteries compared to pregnant non-smokers. The effect of the degree of nicotine addiction on this hemodynamics was also analyzed. An observational cross-sectional study was conducted in 98 chronic pregnant smokers and 102 pregnant non-smokers without known diseases. Doppler study was performed for measuring pulsatility index (PI) and resistance index (RI) of UtA, UmA and MCA. Fagerström and exhaled carbon monoxide (COex) tests were used to evaluate the degree of nicotine dependence. Comparison of Doppler indexes between the two groups showed that only UtA RI and UmA PI had significant effect (p<0.001 and p=0.032, respectively), with higher values in pregnant smokers than non-smokers, indicating vasoconstriction and increased impedance in the studied vessels. Fagerström analysis showed that smoking had a positive effect for PI (p=0.045) and RI (p=0.007) of MCA, with significantly decreased indexes in smokers with high and very high dependence compared to low and moderate dependence. COex analysis showed elevated Um PI in moderate vs light smokers (p=0.035) whereas MCA RI was higher in light vs heavy smokers (p=0.024), differing from previous data. Chronic smoking interfered negatively on maternal-fetal vascular hemodynamics, as demonstrated by increased impedance in the maternal uterine and fetal umbilical arteries. Moreover, the greatest exposure to tobacco caused vasodilation effect in the fetal middle cerebral artery, demonstrating that higher nicotine dependence, the greater the maternal-fetal hemodynamic changes.